2016
DOI: 10.1103/physreva.94.053831
|View full text |Cite
|
Sign up to set email alerts
|

Mirror and cavity formations by chains of collectively radiating atoms

Abstract: We search for mirror and cavity-like features of a linear chain of atoms in which one of the atoms is specially chosen as a probe atom that is initially prepared in its excited state or is continuously driven by a laser field. Short chains are considered, composed of only three and five atoms. The analysis demonstrate the importance of the inter atomic dipole-dipole interaction which may lead to a collective ordering of the emission along some specific directions. We examine the conditions under which the radi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The expression "direction of propagation" can be described in a precise probabilistic setting based on either nonlocal antenna theory [48]- [50] or the quantum field-theoretic approach to information [8], [68]- [70], both based on a momentum space approach to computing the far-field radiation pattern [47]. 16 Radiation Mode Center Direction (θ…”
Section: Coupling To Fluctuating Environments and Time-domain Evoluti...mentioning
confidence: 99%
See 1 more Smart Citation
“…The expression "direction of propagation" can be described in a precise probabilistic setting based on either nonlocal antenna theory [48]- [50] or the quantum field-theoretic approach to information [8], [68]- [70], both based on a momentum space approach to computing the far-field radiation pattern [47]. 16 Radiation Mode Center Direction (θ…”
Section: Coupling To Fluctuating Environments and Time-domain Evoluti...mentioning
confidence: 99%
“…In contrast to classical antennas [34], there is no obviously unique way to do this in the quantum scenario. A possible way to do this is by construing the radiation mode density as the ratio of the total energy of modes, whose wavevectors/momenta k(Ω) satisfy the condition Ω ∈ Ω 0 , to the sum of the energy of 16 Use of the momentum space approach in physics to characterize radiation phenomena has a long history and goes back to several decades ago. We don't go into the full details here, but see, e.g., the historically important texts [67], [71], [72].…”
Section: Coupling To Fluctuating Environments and Time-domain Evoluti...mentioning
confidence: 99%
“…The expression "direction of propagation" can be described in a precise probabilistic setting based on either nonlocal antenna theory [48]- [50] or the quantum field-theoretic approach to information [8], [68]- [70], both based on a momentum space approach to computing the far-field radiation pattern [47]. 16 Radiation Mode Center Direction (θ…”
Section: Coupling To Fluctuating Environments and Time-domain Evoluti...mentioning
confidence: 99%
“…In contrast to classical antennas [34], there is no obviously unique way to do this in the quantum scenario. A possible way to do this is by construing the radiation mode density as the ratio of the total energy of modes, whose wavevectors/momenta k(Ω) satisfy the condition Ω ∈ Ω 0 , to the sum of the energy of 16 Use of the momentum space approach in physics to characterize radiation phenomena has a long history and goes back to several decades ago. We don't go into the full details here, but see, e.g., the historically important texts [67], [71], [72].…”
Section: Coupling To Fluctuating Environments and Time-domain Evoluti...mentioning
confidence: 99%
“…Recently, we have shown that the collective behavior of a linear chain of atoms can result in a strong directional emission of photons into well-defined modes [24]. The strong directivity has been predicted without the requirement of the * qgulfam@jazanu.edu.sa † zficek@kacst.edu.sa coupling of the system to some external medium, for example, a nano-wave guide or a fibre.…”
Section: Introductionmentioning
confidence: 99%